Current Status and Recent Achievements of the Sterile Insect Technique Program Against Dengue Vector, Aedes aegypti, in Indonesia - B. Ernawan; H.I. Sasmita; M. Sadar; I. Sugoro (PPIKSN-BATAN, 2019)
Given the facts that Indonesia has suitable environment condition to survival, reproduction and development of the principal mosquito vector for dengue virus, Aedes aegypti, the transmission of dengue virus does routinely occur every year. The sterile insect technique (SIT) as one of the techniques in area-wide integrated pest management (AW-IPM) has been developed to control Aedes aegypti population since 2004. The first 5 years of the program (2004-2009) was focused on mass rearing facility establishment. The lab-work study for the entomological data and field trials were performed in 2010-2014. In 2014-2019, the program was addressed to enhance the mass rearing facility to increase sterile male production and strengthening the networking throughout the involvement in the regional and interregional program coordinated by International Atomic Energy Agency (IAEA). The main future challenge of the SIT program against Aedes aegypti is developing the capacity building and strong commitment of all stakeholders i.e. the Ministry of Health, the universities, the research institutes and the public. In the future work plan, the pilot project design to proof the concept of the SIT is strongly recommended to obtain a firm, unbiased and strong results as the consideration for the decision maker to create the Aedes control program in Indonesia.